An overview of the experimental techniques for characterization of laser-welded metal joints. (2021) - Jayanthi, A.; Venkataramanan, K.; Kumar, K. Suresh
Graphical abstract: Abstract: The author undergone the research program on laser welding of combination of similar stainless steel and dissimilar stainless steel-steel and that are successfully welded as butt joints followed by an optimization process of operating parameters using the computational model. As a part of the research, it has decided to study microstructure across the weld joint and to study mechanical properties to qualify the weld joints. This paper gives an overview of the method of sample preparation of weld joints for metallurgical examinations using various microscopic and X-ray diffraction techniques. Also, about the destructive testing methods such as tensile test, impact test, bend test and hardness test to qualify the weld joint. X-ray radiography and ultrasonic flaw detector techniques reviewed from theoretical and practical point of view, that are proven non-destructive tests to detect the internal flaws of laser weld specimens with high precision.